(untitled) (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
This reseach form is survey reseach which is done to see the teacherV¶ ability in understanding punctuation.Tecniques in getting data is that 30 valid questions are given to the teachers. The samples in this reseach are 81 teachers in Tampan district with the level of precision 10%. the teachers¶V ability in Tampan district were analyzedbased on category. Among 81 teachers 1 teacher (1,23%) gotthe best category, 31 teachers (38,27%) gotgood, 38teachers (46,91) gotfair category , and 11 teachers (13,58) gets less category. Those results were got from the test that was given to the primary school teachers in Tampan district. The average score is 63,5 with fair category.This shows that primary school teachers did not pass based on classical completeness 39,50% then